Identifikasi Siswa Beresiko Disleksia Di Sekolah Dasar - Desrianti Sapitri; Muhammad Mukhlis (Bale Literasi: Lembaga Riset, Pelatihan & Edukasi, Sosial, Publikasi, 2025)
Dyslexia is a neurological disorder that affects the ability to read and process written language in elementary school-aged children. This study aims to identify categories of students at risk of dyslexia and analyze teacher strategies in addressing learning difficulties at SDN 004 Terantang Manuk. The study used a qualitative approach with a case study type conducted in December 2025. The sample was selected purposively involving four homeroom teachers of grades III, IV, V, and VI as key informants. The research instruments included semi-structured interview guidelines and an observation checklist. Data were collected through in-depth interviews and passive participant observation, analyzed through data reduction, data presentation, and conclusion drawing. Data validity was guaranteed through triangulation of sources, techniques, and time. The results showed that students at risk of dyslexia displayed characteristics in three aspects: (1) Academic: difficulty recognizing letters, low reading speed, difficulty understanding reading, and poor writing quality; (2) Cognitive: slow to learn, short-term memory impairment, and limited vocabulary; (3) Behavioral and emotional: easily distracted, low motivation, and low self-confidence. Teacher strategies include a multisensory learning approach, individualized guidance, intensified reading practice, an emotional approach, and a positive attitude. Obstacles faced include internal factors such as lack of concentration and external factors such as minimal parental guidance. Research implications include the need for teacher training, the development of a referral system with professional services, parent education, the provision of adaptive learning resources, and the implementation of inclusive education policies in accordance with Ministerial Regulation of the Ministry of Education, Culture, Research, and Technology No. 48 of 2023.